Co-expression of glutamatergic and autism-related genes in the hippocampus of male mice with disturbances of social behavior - I. L. Kovalenko; A. G. Galyamina; D. A. Smagin; N. N. Kudryavtseva (Вавиловский журнал генетики и селекции)
There is a hypothesis of the involvement of the glutamatergic system in the development of autism. It has been shown that the chronic experience in daily intermale confrontations leads to disturbances in social behavior: a decrease in communicativeness, disturbances of socialization, emergence of stereotypical behaviors that can be considered as symptoms of the autistic spectrum disorders. So, the aim of this study was to investigate changes in the expression of glutamatergic (GG) and autism-related (GA) genes in the hippocampus of animals with impaired social behavior caused by repeated experience of social defeat or aggression in daily agonistic confrontations. To form groups of animals with contrasting behaviors, a model of sensory contact (chronic social stress) was used. The collected brain samples were sequenced at JSC Genoanalytica (http://genoanalytica.ru/, Moscow, Russia). Transcriptomic analysis revealed a down-regulation of autism-related (Shank3, Auts2, Ctnnd2, Nrxn2) and glutamatergic (Grm4) genes in aggressive mice. At the same time, the expression of GA-related genes (Shank2, Nlgn2, Ptcdh10, Reln, Arx) and GG genes (Grik3, Grm2, Grm4, Slc17a7, Slc1a4, Slc25a22) excluding Grin2a was increased in defeated mice. Correlative analysis revealed a statistically significant association between GG and GA expression. These results can serve as a confirmation of the participation of the glutamatergic system in the pathophysiology of the autistic spectrum disorder.